Can we still call OPEC a cartel? : - Ali, Dalia (2017)
This paper raises the question whether OPEC actually acts like a cartel, given the fact that there were many controversy surrounding the organization due to its coordination failures, which resulted to an oil glut between 2014-2016. Consequently, the oil industry experienced a dramatic decline in oil prices due to the oil surplus. A comparison was made between OPEC's allocated quotas, and its actual oil production to investigate whether the members of the organization adhere to the assigned quota, to achieve highest possible prices.